2021
DOI: 10.3390/curroncol28060363
|View full text |Cite
|
Sign up to set email alerts
|

RELIEF: A Digital Health Tool for the Remote Self-Reporting of Symptoms in Patients with Cancer to Address Palliative Care Needs and Minimize Emergency Department Visits

Abstract: The lack of timely symptom reporting remains a barrier to effective symptom management and comfort for patients with cancer-related palliative care needs. Poor symptom management at home can lead to unwanted outcomes, such as emergency department visits and death in hospital. We developed and evaluated RELIEF, a remote symptom self-reporting app for community patients with palliative care needs. A pilot feasibility study was conducted at a large, community hospital in Ontario, Canada. Patients self-reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…This participatory design and co-creation mode is also considered central to ensuring equity in digital health intervention ( 124 , 125 ). Bhargava et al ( 126 ) confirmed the possibility of cost reduction through digital technology introducing a digital remote symptoms self-reporting application. The economic saving was over 62,000 dollars in a pilot study with 13 patients affected by cancer and receiving palliative care ( 126 ).…”
Section: Discussionmentioning
confidence: 98%
“…This participatory design and co-creation mode is also considered central to ensuring equity in digital health intervention ( 124 , 125 ). Bhargava et al ( 126 ) confirmed the possibility of cost reduction through digital technology introducing a digital remote symptoms self-reporting application. The economic saving was over 62,000 dollars in a pilot study with 13 patients affected by cancer and receiving palliative care ( 126 ).…”
Section: Discussionmentioning
confidence: 98%
“…K was 0.89 with excellent agreement. Thirteen studies were included, of which nine were quantitative [47][48][49][50][51][52][53][54] (one was a protocol used to evaluate new software [55]), two were qualitative [56,57] and two had a mixed-method design [58,59]. The search and decision-making process is described using the PRISMA flow diagram [43] in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Two studies reported the use of smartphones [55,57], and two used computers [58,59]. Finally, in two studies, the e-PROMS were usable on any device [47,50].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Availability of the digital health device for the reporting of the symptoms in patients with cancer to attend palliative care needs results in the reduction of the number of emergency department visits and thereby reduced health care costs (Bhargava et al, 2021). There is promising evidence to use mobile health apps to provide expanded and enhanced health care services to individuals and communities, taking advantage of the growing usage of mobile phones among diverse populations (Källander et al, 2013).…”
Section: Introductionmentioning
confidence: 99%